The Role of Hindu Mandirs in Addressing Intimate Partner Violence Among South Asian American Communities - Reddy, Swathi M. (Violence against women, 2024)
There is a growing body of literature that documents high rates of intimate partner violence within South Asian American communities, indicating a critical need for research that can respond directly to this issue. From a socioecological perspective, Hindu temples can influence members’ behaviors at multiple levels of change and thus may be important sites of collaboration for the prevention of intimate partner violence. Through in-depth qualitative interviews with South Asian families, temple leaders, and community stakeholders, this study indicates that Hindu temples have tremendous capacity to significantly impact intimate partner violence within South Asian American communities.